Areawide management of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), using selected cover crop plants - Robert L. Meagher; Rodney N. Nagoshi; Shelby J. Fleischer; John K. Westbrook; David L. Wright; J. Bradley Morris; James T. Brown; Amy J. Rowley (CABI Agriculture and Bioscience)
Abstract Background Fall armyworm, Spodoptera frugiperda (J. E. Smith) is a migratory moth that annually migrates northward each spring from sites in southern Florida and southern Texas. This caterpillar pest feeds on and damages row, turf and vegetable crops in the eastern and central U.S. Before migrating in spring, it feeds on cover crops in central and eastern Florida and expands its populations. Our objective was to use multi-year studies to compare fall armyworm populations that develop in cover crop plants. Methods A series of field experiments and a laboratory feeding study were conducted to compare infestation and feeding and of fall armyworm on different cover crop plants. Field experiments had plots planted with corn (Zea mays L.), sorghum-sudangrass [Sorghum bicolor (L.) Moench], a standard cover crop in Florida, and two alternative cover crops, sunn hemp (Crotalaria juncea L.) and cowpea [Vigna unguiculata (L.) Walpers spp. unguiculata]. Another trial compared populations in sorghum-sudangrass and in mixtures of sorghum-sudangrass with buckwheat (Fagopyrum esculentum Moench) or pearl millet (Cenchrus americanus (L.) Morrone). Fall armyworm larvae were fed and allowed to develop on different sunn hemp germplasm in a laboratory trial. Results Field populations of fall armyworm were highest on corn, followed by sorghum-sudangrass. Sunn hemp and cowpea had larval populations 70–96% less than on sorghum-sudangrass, suggesting replacement of this cover crop with either plant species might help reduce areawide populations of resident or migratory fall armyworm. Larvae collected from cover crop plots had parasitism levels that averaged 30%, with Chelonus insularis (Hymenoptera: Braconidae) emerging as the most commonly-collected species. Larval feeding on different sunn hemp germplasm lines resulted in no difference in weight gain. Conclusions Replacing sorghum-sudangrass with sunn hemp varieties or germplasm should be acceptable as a replacement cover crop for areawide management of fall armyworm.